(untitled) (Revista Eletrônica Debates em Educação Científica e Tecnológica, 2022)
The aim of this work is to reflect about teaching of isometries and paving during the construction of geometric patterns using the technique Girih present in the ornamentation of the Islamic constructions. It is an exploratory research that, through an intensive bibliographical research, was constructed as a pedagogical proposal with 6 activities, developed with 36 students of the first year of High School in a mathematical leveling bias. The analysis of the results was carried out based on the assumptions of Ethnomathematics. The results indicate a good understanding of the characteristics of the types of paving; resourcefulness in the use of computational paving resources; perception that, in the context of Islamic art, there is an efficient construction strategy characteristic of the Islamic world; increased understanding of the geometric patterns of Islamic art through the Girih technique and growth in students’ curiosity regarding the paving and isometries present in Islamic art.